SEPARATISM IN IDEOLOGY AND ACTIVITIES OF FLEMISH RIGHT-WING POPULIST PARTIES - P. V. Oskolkov (MGIMO University Press, 2017)
The article is devoted to the issue of the Flemish separatism, including autonomism and independism (the latter aiming at the creation of own power center), and how it is reflected in the programs of the Flemish right-wing populist parties. The author presents a brief history of the phenomenon; Flemish separatism is seen in the context of the European integration and in comparison with other separatist movements. Having been articulated politically in 1990s, Flemish separatism is now an inherent part of the right-wing populist party programs: of the Flemish Bloc program (since 2004 it is Flemish Interest) as an independence appeal, and of the New Flemish Alliance program as a call for further state reforming, aiming at the creation of a confederative system. A number of Flanders independence plans have been elaborated, whose authors posit that it is not Flanders that should quit the federation, but Belgium should officially disintegrate into two parts (because only in this case the French-speaking part of the country will not become the sole heir of the federation). The separatists usually see the EU as an institutional barrier; however, its role is acknowledged in the strengthening of regions’ position in the entireEurope. The elements that should keep the Belgian federation intact are not de facto functioning properly; however, gaining full independence would only fix the de jure already existing administrative and political split, and would also create a number of administrative problems. That is why the percentage of the Flemish independence proponents has declined recently, and the Belgian federation is now in a certain “break-even point” that can be distorted by the right-wing populist parties.